Assessment of lumbosacral kyphosis in spondylolisthesis: a computer-assisted reliability study of six measurement techniques - Glavas, Panagiotis (Springer-Verlag, 2008)
Although recognized as an important aspect in the management of spondylolisthesis, there is no consensus on the most reliable and optimal measure of lumbosacral kyphosis (LSK). Using a custom computer software, four raters evaluated 60 standing lateral radiographs of the lumbosacral spine during two sessions at a 1-week interval. The sample size consisted of 20 normal, 20 low and 20 high grade spondylolisthetic subjects. Six parameters were included for analysis: Boxall’s slip angle, Dubousset’s lumbosacral angle (LSA), the Spinal Deformity Study Group’s (SDSG) LSA, dysplastic SDSG LSA, sagittal rotation (SR), kyphotic Cobb angle (k-Cobb). Intra- and inter-rater reliability for all parameters was assessed using intra-class correlation coefficients (ICC). Correlations between parameters and slip percentage were evaluated with Pearson coefficients. The intra-rater ICC’s for all the parameters ranged between 0.81 and 0.97 and the inter-rater ICC’s were between 0.74 and 0.98. All parameters except sagittal rotation showed a medium to large correlation with slip percentage. Dubousset’s LSA and the k-Cobb showed the largest correlations (r = −0.78 and r = −0.50, respectively). SR was associated with the weakest correlation (r = −0.10). All other parameters had medium correlations with percent slip (r = 0.31–0.43). All measurement techniques provided excellent inter- and intra-rater reliability. Dubousset’s LSA showed the strongest correlation with slip grade. This parameter can be used in the clinical setting with PACS software capabilities to assess LSK. A computer-assisted technique is recommended in order to increase the reliability of the measurement of LSK in spondylolisthesis.